KEMAMPUAN BERBAHASA ANAK USIA 6 TAHUN DALAM BERCERITA (ASPEK SINTAKSIS) - Salsabila, Tasya (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
This study reviews the children's language ability in storytelling that is studied using the field of syntactic study. The purpose of this study is to determine the extent to which a child can master a sentence. The method used for this research is descriptive qualitative method. This method describes the results of recorded transcripts for analysis. The results of this analysis show that children in telling stories are more likely to use news sentences in conveying their experiences.Keyword: language, storytelling, and syntax.